2018
DOI: 10.1039/c7tc05488b
|View full text |Cite
|
Sign up to set email alerts
|

A highly polarization sensitive antimonene photodetector with a broadband photoresponse and strong anisotropy

Abstract: Photodetectors based on two-dimensional materials have shown impressive performance including fast and broadband photoresponse and high responsivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(32 citation statements)
references
References 35 publications
0
30
1
1
Order By: Relevance
“…155 Promising indications of broadband use of antimonene as a photodetector or optical modulator have been shown recently. 181,182 It was commented earlier by Xu et al 183 that significant absorption from the visible region to the ultraviolet region can be observed in aw-Sb, while Ares et al 62 reviewed its properties and commented on Sb to have a suitable tunable bandgap for use in optoelectronics. In another study by Singh et al, 171 it was found via the dielectric function and electron loss spectra that plasmon energies around 9 eV and parts of the electromagnetic spectrum make antimonene behave like a metal in terms of reflectivity of light.…”
Section: Antimonenementioning
confidence: 99%
“…155 Promising indications of broadband use of antimonene as a photodetector or optical modulator have been shown recently. 181,182 It was commented earlier by Xu et al 183 that significant absorption from the visible region to the ultraviolet region can be observed in aw-Sb, while Ares et al 62 reviewed its properties and commented on Sb to have a suitable tunable bandgap for use in optoelectronics. In another study by Singh et al, 171 it was found via the dielectric function and electron loss spectra that plasmon energies around 9 eV and parts of the electromagnetic spectrum make antimonene behave like a metal in terms of reflectivity of light.…”
Section: Antimonenementioning
confidence: 99%
“…46 Promising indications of antimonene's broadband use as a photodetector or optical modulator have been shown recently. 47,48 Bismuthene's optical properties have not been vastly investigated yet, with only a few recent examples of electric field applications or its potential as a photonic-based device, 45,[49][50][51] hence the light-matter interaction within 2D bismuthene remains an area of interest. While the dynamical stability, electronic structure and topological features of SL BiSb binary compounds have been studied actively, 34,35,[52][53][54][55][56] very little is known about their optical properties.…”
Section: Current State Of the Problemmentioning
confidence: 99%
“…Inspired by a few preliminary studies, the anisotropy effects and the unique properties of pnictogen on the device performances have been extensively investigated in experiment and theory [59, 78, 79]. For instance, anisotropic photocurrent generation in black phosphorus FETs has been investigated through resolved polarization-dependent photocurrent characterization [80].…”
Section: Integration and Characterization Of 2d Pnictogen Fetsmentioning
confidence: 99%